The environmental education approach in the teacher-student relationship in public schools in Parauapebas in the State of Pará, Brazil - Oliveira, Jhulia Rodrigues de (2020)
Starting from the research, we seek to analyze the non-educational difficulties faced by teaching hairs in the insertion and development of environmental education in public schools of fundamental education in the city of Parauapebas, Pará. Initially, we applied questionnaires together with pedagogues on the issues of pollution, burning, importance of the selective queue, recycling, consumption and waste of water, among others, it was possible to develop a research of how much quali-quantitative aiming or raising of data for a better understanding do subject and also establish educational parameters possible not environmental question. According to the research, approximately 55% two teachers frequently approach environmental education in the classroom, or advancement of individual competences and perceptible not day by day of the individual, despite the effort, we also report certain disinterest in the part of the learner about 60%, perhaps in the absence of diversities of exercises within the classroom or attached some efforts as in the absence of incentive from the municipality or other activities. Logo perceives a need for restructuring of the organization for a qualification not only professional, but also that it bears a greater absorption of content from part two students, since it requires specific attention for this age group. In this way, begin to encourage a more critical knowledge of two students, in order to reflect on a conscious society to obtain a minimization of degradation in nature.